Agroforestry-Based Ecosystem Services - van Noordwijk, Meine (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
As a dynamic interface between agriculture and forestry, agroforestry has only recently been formally recognized as a relevant part of land use with 'trees outside forest' in important parts of the world-but not everywhere yet. The Sustainable Development Goals have called attention to the need for the multifunctionality of landscapes that simultaneously contribute to multiple goals. In the UN decade of landscape restoration, as well as in response to the climate change urgency and biodiversity extinction crisis, an increase in global tree cover is widely seen as desirable, but its management by farmers or forest managers remains contested. Agroforestry research relates tree-soil-crop-livestock interactions at the plot level with landscape-level analysis of social-ecological systems and efforts to transcend the historical dichotomy between forest and agriculture as separate policy domains. An 'ecosystem services' perspective quantifies land productivity, flows of water, net greenhouse gas emissions, and biodiversity conservation, and combines an 'actor' perspective (farmer, landscape manager) with that of 'downstream' stakeholders (in the same watershed, ecologically conscious consumers elsewhere, global citizens) and higher-level regulators designing land-use policies and spatial zoning.